Statistical modeling of zaltoprofen loaded biopolymeric nanoparticles: Characterization and anti-inflammatory activity of nanoparticles loaded gel - Shah, Hirva A; Patel, Rakesh P (International Journal of Pharmaceutical Investigation)
Objective: The main objective of this study is to formulate polymeric nanoparticles (NPs) loaded with zaltoprofen, an NSAID drug. The optimization, in terms of polymer concentration, stabilizer concentration and pH of the formulation was employed by 3-factor-3-level Box-Behnken experimental design. Materials and Methods: The NPs of zaltoprofen were fabricated using chitosan and alginate as polymers by ionotropic gelation. The ionic interaction between the ionic polymers was studied using Fourier transform infrared and differential scanning calorimetry study. Result: For different formulation the average particle size ranged between 156 ± 1.0 nm and 554 ± 2.8 nm. The drug entrapment ranged between 61.40% ± 3.20% and 90.20% ± 2.47%. The ANOVA results exhibited that all the three factors were significant. The resultant optimized batch was characterized by particle size 156.04 ± 1.4 nm, %entrapment efficacy 88.67% ± 2.0%, zetapotential + 25.3 mV and polydispersity index 0.320. The scanning electron microscopy showed spherical NPs of average size 99.5 nm. The optimized NPs were loaded in carbopol gel, which was subjected to study of drug content, viscosity, spreadability, in vitro drug diffusion and in vivo antiinflammatory test on rats. Conclusion: This study showed that zaltoprofen NPs prepared using the ratio of polymer CS:AG:1:1.8, stabilizer concentration 0.98% and pH 4.73 was found to be of optimized particle size, maximum drug entrapment. The NPs loaded gel showed controlled release for 12 h following Korsmeryer-peppas model of the diffusion profile. The in vivo antiinflammatory study showed prolonged effect of NPs loaded gel for 10 h.
Keywords: Antiinflammatory study; Box-Behnken; chitosan nanoparticle; diffusion study; scanning electron microscopy